Lipid Metabolism Profiles in Rheumatic Diseases - Chen, Weilin; Wang, Qi; Zhou, Bin; Zhang, Lihua; Zhu, Honglin (Frontiers in Pharmacology, 2021)
Rheumatic diseases are a group of chronic autoimmune disorders that involve multiple organs or systems and have high mortality. The mechanisms of these diseases are still ill-defined, and targeted therapeutic strategies are still challenging for physicians. Recent research indicates that cell metabolism plays important roles in the pathogenesis of rheumatic diseases. In this review, we mainly focus on lipid metabolism profiles (dyslipidaemia, fatty acid metabolism) and mechanisms in rheumatic diseases and discuss potential clinical applications based on lipid metabolism profiles.